Determinants of Infant Feeding Practices Among HIV-Infected Mothers in Urban Kano, Nigeria. (August 2019) - Iliyasu, Zubairu; Galadanci, Hadiza S.; Iliyasu, Miyassaratu L.; Babashani, Musa; Gajida, Auwalu U; Nass, Nafisa S.; Aliyu, Muktar H.
Background: Despite advances in prevention of mother-to-child HIV transmission, infants in Africa remain at risk of HIV acquisition from inappropriate feeding practices. Research aims: To assess maternal knowledge and predictors of appropriate infant feeding practices among HIV-infected mothers attending a tertiary facility in Kano, Nigeria. Method: A cross section of 203 HIV-positive mothers were interviewed using structured, pretested survey questionnaires. Knowledge scores and infant feeding practices were analyzed. Multivariate logistic regression was employed to ascertain independent correlates of infant feeding practices in the study sample. Results: Over a third (37.4%) of the participants were aware of the risk of HIV transmission through breastfeeding. The proportion of participants with good, fair, and poor knowledge of recommended feeding options for HIV-exposed infants was 4.4%, 73.4%, and 22.2%, respectively. About three in four participants (73.9%) breastfed their index infants exclusively for the first six months. Approximately 7.4% of respondents practiced mixed feeding (breastfeeding plus infant formula). Counseling on infant feeding (Adjusted Odds Ratio [AOR] = 2.16, 95% Confidence Interval [CI] = [1.58, 4.15]) and hospital delivery (AOR = 3.02, 95% CI = [2.67, 7.84]) predicted appropriate infant feeding practice. Conclusion: Appropriate infant feeding practices were significantly associated with prior infant feeding counseling and delivery in a hospital setting. HIV-infected mothers in this setting should receive counseling on infant feeding early in their pregnancy and be educated on the importance of hospital delivery.